'My primary purpose is to protect the unborn child': Understanding pregnant women's perceptions of maternal vaccination and vaccine trials in Europe. Issue 39 (15th September 2021) - Karafillakis, E.; Paterson, P.; Larson, H.J.
Abstract: Despite the important benefits of maternal vaccination for pregnant women and newborns, vaccination uptake is low in many European countries. Differences in vaccination policies and recommendations, as well as concerns about vaccine safety can partly explain inadequate coverage rates and women's hesitancy to get vaccinated during pregnancy. This study aims to explore pregnant women's experiences, decision-making processes and perceptions towards maternal vaccination and maternal vaccine trials in France, Germany, Italy, Spain and the United Kingdom. Qualitative interviews and focus groups were conducted with 258 pregnant women identified through local research panels and snowballing. Topic guides translated in local languages were designed to explore women's awareness and perceptions of maternal vaccination, and willingness to participate in vaccine trials during pregnancy. A thematic analysis was conducted. Pregnant women were found to have low awareness about maternal vaccination, with many reporting not having received a recommendation to vaccinate from their doctors. Strong trust in health professionals indicate that strengthened recommendations could improve vaccination uptake. Vaccination decision-making in pregnancy was described in the context of a highly emotional period, generating anxiety and fears around the safety of vaccines. Pregnancy was also discussed as a period during which women develop nurturing and protective identities. However, depending on the information they received as well as influences from experts, families and peers, women either perceived vaccination as a threat to their babies' safety or as a means to protect them. Attitudes towards maternal vaccine trials were less ambiguous, with most pregnant women strongly rejecting the notion of taking part in trials. While strategies to improve pregnant women's awareness and perceptions of maternal vaccination are needed, it is equally important to understand why healthcare professionals may not be recommending vaccination. More coordinated strategies across Europe could help strengthen communication and trust in maternal vaccination.